(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
The paper deals with the topic of communicating bad news concerning di-agnosis and prognosis to severely or terminally ill patients with particular regards to oncology and chronical-degenerative illnesses. Communicating bad news is a precise ethical and deontological duty and this process should take into consideration the patient’s life and past experiences, in order to build the best therapeutic relationship possible. It also requires professional skills that engage the whole medical and nursing staff. To this end, the paper describes a communicative approach largely adopted in Palliative Care, which could also be applied in other healthcare fields where the doctor-patient relationship could include the communication of bad news (such as in Intensive Care). The paper indicates also some of the most common mistakes in the communication of bad news and proposes some tips to avoid them.